Dynamic increase factors for Radiata pine CLT panels subjected to simulated out-of-plane blast loading. (15th December 2020) - Van Le, Tu; Ghazlan, Abdallah; Ngo, Tuan; Remennikov, Alex; Kalubadanage, Dulara; Chern Jinn Gan, Edward
Highlights: The dynamic response of cross laminated timber (CLT) panels was investigated. Simulated blast tests were conducted on the CLT panels using a shock tube. Analytical/numerical models were used to predict the dynamic increase factor on stiffness (DIFE ). DIFs were predicted using the Young's modulus. The analytical and numerical models agreed well with the experiments. Abstract: The construction industry, which accounts for almost 20% of Australia's carbon emissions, is responding to climate change by increasing the demand for sustainable and environmentally friendly materials. Cross-laminated timber (CLT) is an innovative eco-friendly engineering material that can satisfy this demand due to its excellent properties, including fire and seismic resilience, natural insulation and lightweight, to name a few. This study presents the results of 8 blast tests, which were conducted on two types of Radiata pine CLT panels sourced in Australia. The CLT panels were subjected to simulated blast loads from a shock tube apparatus. The dynamic increase factor (DIFE ) of the panels was quantified by comparing their stiffness in the dynamic and static loading regimes. Single degree of freedom (SDOF) and numerical models were developed to predict the elastic response of the CLT panels. Interestingly, the SDOF model predicted DIFE from 1.12 to 1.57 whilst the numerical model predicted DIFE from 1.05 to 1.43 . The experimental and analytical results can supplement the development of design guidelines for predicting the behavior of Australian Radiata pine CLT panels under blast loading.